Synaptopathies in Developmental and Epileptic Encephalopathies: A Focus on Pre-synaptic Dysfunction - Spoto, Giulia; Valentini, Giulia; Saia, Maria Concetta; Butera, Ambra; Amore, Greta; Salpietro, Vincenzo; Nicotera, Antonio Gennaro; Di Rosa, Gabriella (Frontiers in Neurology, 2022)
The proper connection between the pre- and post-synaptic nervous cells depends on any element constituting the synapse: the pre- and post-synaptic membranes, the synaptic cleft, and the surrounding glial cells and extracellular matrix. An alteration of the mechanisms regulating the physiological synergy among these synaptic components is defined as “synaptopathy”. Mutations in the genes encoding for proteins involved in neuronal transmission are associated with several neuropsychiatric disorders, but only some of them are associated with Developmental and Epileptic Encephalopathies (DEEs). These conditions include a heterogeneous group of epilepsy syndromes associated with cognitive disturbances/intellectual disability, autistic features and movement disorders. This review aims to elucidate the pathogenesis of these conditions, focusing on mechanisms affecting the neuronal presynaptic terminal and its role in the onset of DEEs, including potential therapeutic approaches.